Guidelines for Using Development of Competencies of School Administrators in the Digital Age according to the Trisikkha Principles of the Educational Opportunity Expansion Schools in Noen Kham District, Chainat Province: - - Panrungmanee, Jeeranuch; Metheevachatra, Anond; Thuenchang, Worrakrit (Mahachula Academic Journal, 2026)
The objectives of this research were 1) to study the digital competencies of school administrators in opportunity expansion schools; and 2) to propose guidelines for developing the digital competencies of school administrators in opportunity expansion schools based on the Trisikkha principle. This study employed a mixed-methods research design. The sample was obtained through purposive sampling, consisting of 11 key informants. The research instruments included a questionnaire with a reliability of 0.97 and an interview form. Data were analyzed using frequency, percentage, mean, and standard deviation, while qualitative data were examined through content analysis. The results were as follow: 1) The overall digital leadership competencies of school administrators in opportunity expansion schools in Noen Kham District, Chai Nat Province, is at a high level = 4.41, = 0.12). When considering each aspect, it was found that the aspect of communication and digital networking for learning had the highest average, at the highest level ( = 4.55, = 0.14), followed by the aspect of ethics and digital safety, at a high level ( = 4.46, = 0.19). The aspect with the lowest average was developing the school into a digital organization, at a high level ( = 4.33, = 0.26). 2) The guidelines for developing these digital leadership competencies based on the Trisika principle, the study revealed eighteen guidelines across six aspects with 3 guidelines for each aspect. These include 3 guidelines for the first aspect on digital innovation creation and 3 guidelines for the second aspect on communication and digital networking for learning. The third aspect regarding critical digital literacy contains 3 guidelines and the fourth aspect on developing the school into a digital organization also has 3 guidelines. Additionally, there are 3 guidelines for the fifth aspect concerning the ability to use digital technology and 3 guidelines for the sixth aspect which focuses on digital ethics and safety.